Super-osmosis separation membrane as well as preparation method and application thereof
By dividing the surface layer of affinity molecules and ultrafast transport layers in the separation membrane, the problems of high energy consumption and interface defects of bio-based platform compounds in the prior art are solved, and the separation effect with high efficiency and low energy consumption is achieved.
Patent Information
- Application Number
- CN202311252659.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-26
AI Technical Summary
The prior art has problems of high energy consumption and complex process in the separation process of bio-based platform compounds, and the organic-inorganic hybrid films are limited by interface defects in separation performance.
By dividing the separation membrane structure into an affinity molecular surface layer based on organic polymers and an ultrafast transport layer based on biligand metal organic framework materials, the deconstruction-assembly construction idea is adopted to avoid the occurrence of interface defects, thereby optimizing the enrichment and separation performance of the membrane.
The separation of bio-based platform compounds with low energy consumption and high efficiency is achieved, avoiding the limitation of separation performance by interface defects, and improving the permeability and separation selectivity of the membrane.
Smart Images

Figure BDA0004470773390000071 
Figure BDA0004470773390000072 
Figure BDA0004470773390000073
Abstract
Description
Technical Field
[0001] The invention relates to a super permeability separation membrane and a preparation method and application thereof, belonging to the field of material chemical separation. Background Art
[0002] Excessive consumption of fossil energy has caused environmental degradation and energy depletion, and it is urgent to seek renewable and sustainable energy resources. Bio-based platform compounds (such as polyols and furan compounds) prepared by biorefining technology can be used as raw materials to build a variety of biofuels and high-value chemicals, opening up the biomass chain economy. However, the separation of bio-based platform compounds still faces huge challenges. Bio-based platform compounds are mainly derived from acid-catalyzed hydrolysis of sugar compounds, produced in dilute aqueous solutions, and have a high boiling point. Traditional separation methods (such as distillation, gas stripping, and vapor phase adsorption technology) involve phase changes of the components to be separated, and the process is relatively complex and energy-intensive. In contrast, the pervaporation membrane separation method has lower energy consumption and higher efficiency, and is more suitable for the efficient separation of bio-based platform compounds. The use of pervaporation membranes to efficiently enrich low-concentration alcohols and other organic products in water requires further optimization of membrane construction materials on the one hand, and optimization of membrane structure construction methods on the other hand.
[0003] As far as membrane materials are concerned, metal-organic frameworks (MOFs) are a type of highly ordered porous organic-inorganic hybrid materials formed by coordination between metal ions (clusters) and organic ligands. Zeolitic imidazolate frameworks (ZIFs), as a subclass of MOF materials, are widely used in the separation field due to their special thermal stability, chemical stability and microporous properties. In order to further adjust the framework structure and physicochemical properties of ZIF materials in order to further optimize their application potential in separation systems (Eum K. JACS, 2015, 137: 4191). In recent years, it has been reported that the preparation of dual-ligand ZIF materials by introducing another ligand into the existing ZIF structure for the growth and preparation of polycrystalline membranes has improved the permeability of propylene molecules in propylene / propane separation systems (Hillman F. ACS Appl. Mater. Interface, 2019, 11: 18377). Dual-ligand materials synthesized by mixed ligands provide new design ideas for regulating the skeleton and physical and chemical properties of materials, and are expected to provide new opportunities in the application of separation membrane construction.
[0004] In the process of separation membrane construction, the construction of membrane structure is another key to achieve better organic affinity performance. Traditional pervaporation membrane materials used for preferential permeation of organic matter mainly include inorganic molecular sieve membrane materials, organic polymer membrane materials and organic-inorganic hybrid membrane materials. Although inorganic molecular sieve membranes have good thermal stability, chemical stability and mechanical strength, the preparation of complete, continuous and dense molecular sieve membranes has high requirements for process and substrate. Organic polymer materials have the advantages of good flexibility and film-forming properties, high selectivity, many varieties, simple preparation process and mature process, but the stability and mechanical strength still need to be further improved. Organic-inorganic hybrid membranes refer to mixed matrix membranes (MMMs) obtained by adding inorganic particles to an organic matrix. They can effectively combine the advantages of both and are one of the main development directions in the field of pervaporation membrane separation in the future. If interface defects are formed at the interface of the mixed matrix membrane, the separation performance will not reach the expected target, thereby restricting the development of organic-inorganic hybrid membranes to enrich organic matter. Summary of the invention
[0005] The purpose of the present invention is to provide a super permeability separation membrane and a preparation method and application thereof. The super permeability separation membrane proposed in the present invention divides the separation membrane structure into an affinity molecule surface layer based on an organic polymer and an ultrafast transmission layer based on a dual ligand metal organic framework material. The generation of interface defects is avoided through the deconstruction-assembly construction concept, thereby optimizing the enrichment and separation performance of the membrane.
[0006] A super permeability separation membrane comprises an affinity molecule surface layer (hydrophobic molecule shell layer) and an ultrafast transmission layer, wherein the affinity molecule surface layer is located outside the ultrafast transmission layer.
[0007] Based on the above technical solution, further, the surface layer of the affinity molecule is cross-linked polysiloxane or ionic liquid.
[0008] Based on the above technical solution, further, the thickness of the surface layer of the affinity molecule is 0 to 50 nm, and is not 0.
[0009] Based on the above technical solution, further, the ultrafast transport layer is a continuous nanoparticle layer of a dual-ligand metal-organic framework material with a particle size of 10-1000nm (preferably 800-2000nm) or a stacking layer of dual-ligand metal-organic framework nanosheets with a thickness of 1-100nm (preferably 50-100nm).
[0010] The present invention also relates to a method for preparing the above-mentioned ultra-permeable separation membrane, comprising the following steps:
[0011] (1) Fully dispersing a dual-ligand metal-organic framework material (dual-ligand MOF material) in butanol to prepare a dispersion liquid, which is referred to as liquid A and set aside; dissolving silicone rubber (hydroxy polymethylphenylsiloxane) in butanol, fully stirring, and preparing a silicone rubber solution, which is referred to as liquid B and set aside; mixing liquid A and liquid B in an ice-water bath to obtain a mixed matrix membrane casting liquid; wherein the mass ratio of the silicone rubber, butanol, and dual-ligand metal-organic framework material is 1:2-10:0.1-0.8; using the dual-ligand metal-organic framework material as a filling particle and blending it with silicone rubber to prepare a casting liquid;
[0012] (2) coating the mixed matrix membrane casting liquid onto the alumina-based membrane to obtain the mixed matrix membrane; constructing an ultrafast transport layer based on the dual-ligand metal organic framework material, and the mixed matrix membrane will undergo a subsequent cross-linking reaction in the next step.
[0013] (3) placing the mixed matrix membrane in an isooctane solution containing a silane coupling agent and a catalyst for interfacial crosslinking at a temperature of 15 to 30° C. for a time of 0.5 h to 72 h, preferably 24 h; in this process, the affinity molecule surface layer is assembled by crosslinking.
[0014] Based on the above technical solution, further, in step (1), the method for preparing the dual-ligand metal-organic framework material comprises the following steps:
[0015] Dissolve one of the nitrates, acetates or halides of divalent metal zinc or cobalt in anhydrous methanol, stir evenly to obtain a metal solution for use. Dissolve 2-methylimidazole and 4,5-dichloroimidazole in anhydrous methanol at the same time, stir evenly to obtain a dual ligand solution for use. Mix the metal solution with the dual ligand solution, react at 20-30°C (preferably 23-25°C) for 0.5-24 hours (preferably 2 hours), centrifuge the obtained product, wash with anhydrous methanol, and obtain a dual ligand metal-organic framework material; wherein the molar ratio of the divalent metal zinc or cobalt ion to the sum of 2-methylimidazole and 4,5-dichloroimidazole is 1:2.
[0016] Based on the above technical solution, further, the concentration of the metal solution is 0.007-0.1 g / ml, preferably 0.007-0.01 g / ml; the concentration of the dual ligand solution is 1*10 -5 ~0.2g / ml, preferably 1*10 -5 ~0.02g / ml.
[0017] Based on the above technical solution, further, the molar ratio of the divalent metal zinc or cobalt, 2-methylimidazole and 4,5-dichloroimidazole is 1:1:1.
[0018] Based on the above technical solution, further, in step (1), the method for preparing liquid A is specifically as follows: solid particles (bi-ligand metal-organic framework material) are added to butanol, and fully dispersed by water bath ultrasound for 1.5 hours to prepare a dispersion.
[0019] Based on the above technical scheme, further, in step (1), the method for preparing the mixed matrix membrane casting liquid is specifically as follows: 3-5 drops of liquid B are added to liquid A for pre-wetting, and liquid A is further evenly dispersed by ultrasonic dispersion using a probe ultrasonic instrument in an ice-water bath, and then all the liquid A treated with the above-mentioned probe ultrasonic treatment is added to the remaining liquid B, while stirring, and the obtained AB mixed liquid is further ultrasonically dispersed by a probe ultrasonic instrument in an ice-water bath to obtain a mixed matrix membrane casting liquid.
[0020] Based on the above technical solution, further, in step (2), the thickness of the aluminum oxide base film is 1-2 mm, and the coating method is a dipping-pulling method, a spin coating method or a blade coating method.
[0021] Based on the above technical solution, a temperature-controlled multilayer immersion-pulling coating machine is further used to construct an ultrafast transport layer based on a dual-ligand metal organic framework material by the immersion-pulling method, and the aluminum oxide-based membrane is immersed and pulled in the mixed matrix membrane casting solution obtained above. The immersion speed is 1-8 mm / s, preferably 1-6 mm / s; the immersion time is 10-60s, preferably 10-20s; the pulling speed is 1-8 mm / s, preferably 1-6 mm / s.
[0022] Based on the above technical scheme, further, in step (3), the silane coupling agent is tetraethoxysilane, the catalyst is dibutyltin dilaurate, and the mass ratio of the silane coupling agent, the catalyst and the isooctane in the isooctane solution containing the silane coupling agent and the catalyst is 1:1-5:10-50, preferably 1:1.3:33.
[0023] The present invention also relates to the protection of the ultra-permeable separation membrane for enriching organic products of low-concentration alcohol or aldehyde in aqueous solution.
[0024] Based on the above technical solution, further, the mass concentration of the low-concentration alcohol or aldehyde in water is 0.01-10%, the alcohol includes methanol, ethanol or butanol, and the aldehyde includes furfural.
[0025] The present invention prepares a dual-ligand MOF material through a one-pot reaction at 20-30°C. The prepared dual-ligand MOF material is an ideal raw material for membrane construction, and has good application potential in the separation field. The preparation method is simple and the conditions are mild. The preparation method provided by the present invention is universal for other hybrid MOF materials.
[0026] Compared with the prior art, the advantages of the present invention are:
[0027] (1) The preparation process is energy-saving and simple, and it is a convenient chemical synthesis method;
[0028] (2) The experimental design is ingenious. By introducing ligands of different topological structures to design and synthesize dual-ligand hybrid MOF ultra-permeable membranes, the construction ideas of hybrid MOF material membranes have been broadened, which has certain guiding significance for other hybrid MOF materials.
[0029] (3) The ultra-permeable membrane of the present invention is expected to meet the practical application needs of the pervaporation separation industry due to its remarkable characteristic of high permeability, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The present invention is attached Figure 5 Size:
[0031] Figure 1 It is the X-ray diffraction pattern of ZIF-8-71-1-1 powder, ZIF-8 and ZIF-71 in Example 1.
[0032] Figure 2 This is the SEM image of the ZIF-8-71-1-1 powder material in Example 1.
[0033] Figure 3 This is a surface SEM image of the ultra-permeable membrane based on ZIF-8-71-1-1 powder in Example 1.
[0034] Figure 4 This is a cross-sectional SEM image of the ultrapermeable membrane based on ZIF-8-71-1-1 powder in Example 1.
[0035] Figure 5 Schematic diagram of a device for testing the separation performance of an ultra-permeable membrane in an embodiment. DETAILED DESCRIPTION
[0036] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0037] Example 1. Synthesis of a dual-ligand material ZIF-8-71-1-1 with a molar ratio of 2-methylimidazole to 4,5-dichloroimidazole = 1:1 and preparation of an ultra-permeable membrane loaded with 30% ZIF-8-71-1 granular material and a cross-linking time of 1 h
[0038] Weigh 0.7g zinc nitrate hexahydrate (Sigma-Aldrich, ≥98%) and dissolve it in 90ml anhydrous methanol solvent, stir and dissolve it as solution 1 for later use. Weigh 0.19g 2-methylimidazole (Sigma-Aldrich, ≥98%) and 0.3g 4,5-dichloroimidazole (Sigma-Aldrich, ≥98%) and dissolve it in 90ml anhydrous methanol solvent, stir and dissolve it as solution 2 for later use. Slowly add solution 1 dropwise to solution 2 with continuous stirring, and react at a constant temperature of 25°C for 2h. After the reaction is completed, transfer the suspension to a centrifuge tube for centrifugation, wash it with anhydrous methanol 3 times, and dry it in a 60°C oven overnight to obtain the product ZIF-8-71-1-1.
[0039] 1.026 g of zinc nitrate hexahydrate (Sigma-Aldrich, ≥98%) was weighed and dissolved in 70 ml of methanol, and the resulting solution was added to 70 ml of a methanol solution containing 2.072 g of 2-methylimidazole, and the mixture was reacted at 25°C for 1 h. After the reaction, the suspension was transferred to a centrifuge tube for centrifugation, washed three times with anhydrous methanol, and dried in a 60°C oven overnight to obtain the product ZIF-8.
[0040] 0.446 g of zinc acetate dihydrate (Sigma-Aldrich, ≥98%) was weighed and dissolved in 90 ml of methanol, and the resulting solution was added to 90 ml of a methanol solution containing 1.315 g of 4,5-dichloroimidazole, and reacted at 25°C for 24 hours. After the reaction was completed, the suspension was transferred to a centrifuge tube for centrifugation, washed three times with anhydrous methanol, and dried in a 60°C oven overnight to obtain the product ZIF-71.
[0041] X-ray diffractometer (XRD) and scanning electron microscope (SEM) were used to characterize the morphology of the dual-ligand MOF material prepared by the present invention, and compared with the morphology of ZIF-8 and ZIF-71. The results are as follows:
[0042] Figure 1 The X-ray diffraction patterns of the ZIF-8-71-1-1 powder, ZIF-8 and ZIF-71 in Example 1 are given, and the patterns show that the synthesized material presents a RHO crystal phase similar to that of ZIF-71.
[0043] Figure 2 This is a SEM image of the ZIF-8-71-1-1 powder material in Example 1. The SEM test results show that the experimentally synthesized ZIF-8-71-1-1 powder has a cubic morphology with nanoparticles attached to the surface, and the particle size is about 1.5 μm.
[0044] The ZIF-8-71-1-1 powder material synthesized by the above method was prepared into a 10% butanol dispersion without drying, and was fully dispersed into a suspension by water bath ultrasound for 1.5 hours. 4.5g of the suspension was weighed and recorded as liquid A for later use. 1.5g of silicone rubber (hydroxypolymethylphenylsiloxane) was weighed and dissolved in 5.95g butanol, and the silicone rubber solution was prepared by full stirring and recorded as liquid B for later use.
[0045] Subsequently, 0.15 ml of liquid B was added to liquid A for pre-wetting, and liquid A was ultrasonically dispersed for 5 minutes using a probe ultrasonic instrument in an ice-water bath to further disperse it evenly. Subsequently, all of the liquid A treated with the probe ultrasonic instrument was added to the remaining liquid B while stirring. The obtained AB mixed solution was further ultrasonically dispersed for 10 minutes using a probe ultrasonic instrument in an ice-water bath to obtain a mixed matrix membrane casting solution, wherein the mass ratio of silicone rubber: butanol: biligand metal-organic framework material particles was 1:6.67:0.3.
[0046] The alumina-based membrane with a diameter of 18 mm and a thickness of 1 mm was immersed and pulled in the AB mixed solution obtained above. The immersion speed was 1 mm / s, the immersion time was 10 s, and the pulling speed was 1 mm / s. The mixed matrix membrane pulled from the casting solution was placed in an isooctane solution of tetraethoxysilane and dibutyltin dilaurate (composed of 0.3 g tetraethoxysilane, 0.4 g dibutyltin dilaurate and 10 g isooctane) for interfacial cross-linking to assemble the affinity molecule surface layer, the reaction temperature was 20 ° C, and the reaction time was 1 h. The above steps were used to prepare three super permeable membranes in parallel for performance testing.
[0047] Figure 3 The surface SEM image of the ultra-permeable membrane based on ZIF-8-71-1-1 powder in Example 1 is given, showing that the prepared ultra-permeable membrane has no obvious defects.
[0048] Figure 4 The cross-sectional SEM image of the super permeable membrane based on ZIF-8-71-1-1 powder in Example 1 is given, showing that the thickness of the prepared super permeable membrane is about 3.76 microns.
[0049] The ability of the super permeable membrane based on ZIF-8-71-1-1 powder to enrich n-butanol from aqueous solution was tested by pervaporation method to evaluate its separation performance. Figure 5As shown, during the test, the raw material liquid in the three-necked flask is n-butanol / water, that is, a dilute n-butanol aqueous solution with a mass fraction of 1.0wt.%, and the test temperature is 80°C. The ultra-permeable membrane is encapsulated in the membrane assembly shown in the figure with a rubber O-ring and extends about 1cm below the surface of the raw material liquid. The back side of the membrane is maintained by an oil pump to maintain the permeation measurement vacuum. The permeate passing through the membrane is collected at specific time intervals in a liquid nitrogen cold trap, and the permeate components are analyzed on a gas chromatograph (7890BAgilent). The enrichment and separation performance of the membrane is evaluated by the following parameters. The performance test results of three parallel membranes are shown in Table 1 below. The test results show that the ultra-permeable membrane has excellent permeability:
[0050]
[0051]
[0052] In formula (1), J is the total flux (kg m -2 h -1 )
[0053] W: permeate mass (kg); Δt is the sampling interval (h); A is the effective separation membrane area (m 2 ). This parameter is used to evaluate the permeability of the membrane.
[0054] In formula (2), SF i / H2O :Separation factor of component i
[0055] Yi: mass fraction of component i in the permeate; Xi: mass fraction of component i in the raw material solution; Y H2O : mass fraction of water in the permeate; X H2O : The mass fraction of water in the raw liquid; Yi and Xi represent the mass fraction of component i in the permeate and the raw liquid, respectively. This parameter is used to evaluate the separation selectivity of the membrane.
[0056] Table 1
[0057]
[0058] Example 2. Synthesis of the dual-ligand material ZIF-8-71-1-1 with a molar ratio of 2-methylimidazole to 4,5-dichloroimidazole = 1:1 and preparation of an ultra-permeable membrane loaded with 30% ZIF-8-71-1 granular material and a cross-linking time of 24 h
[0059] Weigh 0.7g zinc nitrate hexahydrate (Sigma-Aldrich, ≥98%) and dissolve it in 90ml anhydrous methanol solvent, stir and dissolve it as solution 1 for later use. Weigh 0.19g 2-methylimidazole (Sigma-Aldrich, ≥98%) and 0.3g 4,5-dichloroimidazole (Sigma-Aldrich, ≥98%) and dissolve it in 90ml anhydrous methanol solvent, stir and dissolve it as solution 2 for later use. Slowly add solution 1 dropwise to solution 2 and continue stirring, and react at a constant temperature of 25°C for 2h. After the reaction is completed, transfer the suspension to a centrifuge tube for centrifugation, wash it with anhydrous methanol 3 times to obtain the product ZIF-8-71-1-1 particles, prepare it into a butanol dispersion with a mass fraction of 10% without drying, and fully disperse it into a suspension by water bath ultrasound for 1.5h. Weigh 4.5g of the suspension and record it as liquid A for later use. Separately, 1.5 g of silicone rubber (hydroxypolymethylphenylsiloxane) was dissolved in 5.95 g of butanol and stirred thoroughly to prepare a silicone rubber solution, which was recorded as solution B and set aside.
[0060] Subsequently, 0.15 ml of liquid B was added to liquid A for pre-wetting, and liquid A was ultrasonically dispersed for 5 minutes using a probe ultrasonic instrument in an ice-water bath to further disperse it evenly. Subsequently, all of the liquid A treated with the probe ultrasonic instrument was added to the remaining liquid B while stirring. The obtained AB mixed solution was further ultrasonically dispersed for 10 minutes using a probe ultrasonic instrument in an ice-water bath to obtain a mixed matrix membrane casting solution, wherein the mass ratio of silicone rubber: butanol: biligand metal-organic framework material particles was 1:6.67:0.3.
[0061] An alumina-based membrane with a diameter of 18 mm and a thickness of 1 mm was immersed and pulled in the AB mixed solution obtained above. The immersion speed was 1 mm / s, the immersion time was 10 s, and the pulling speed was 1 mm / s. The mixed matrix membrane pulled from the casting solution was placed in an isooctane solution of tetraethoxysilane and dibutyltin dilaurate (composed of 0.3 g tetraethoxysilane, 0.4 g dibutyltin dilaurate and 10 g isooctane) for interfacial cross-linking to assemble the affinity molecule surface layer. The reaction temperature was 20 ° C and the reaction time was 24 h. Three ultra-permeable membranes were prepared in parallel using the above steps for performance testing. The test method is the same as in Example 1.
[0062] The performance test results of three parallel membranes are shown in Table 2 below. The test results show that the ultra-permeable membrane with a cross-linking reaction time of 24 hours also has relatively excellent permeability.
[0063] Table 2
[0064]
[0065] Example 3. Synthesis of the dual-ligand material ZIF-8-71-1-1 with a molar ratio of 2-methylimidazole to 4,5-dichloroimidazole = 1:1 and preparation of an ultra-permeable membrane loaded with 50% ZIF-8-71-1 granular material and a cross-linking time of 1 h
[0066] Weigh 0.14g zinc nitrate hexahydrate (Sigma-Aldrich, ≥98%) and dissolve it in 180ml anhydrous methanol solvent, stir and dissolve it as solution 1 for later use. Weigh 0.38g 2-methylimidazole (Sigma-Aldrich, ≥98%) and 0.6g 4,5-dichloroimidazole (Sigma-Aldrich, ≥98%) and dissolve it in 180ml anhydrous methanol solvent, stir and dissolve it as solution 2 for later use. Slowly add solution 1 dropwise to solution 2 and continue stirring, and react at a constant temperature of 25°C for 2h. After the reaction is completed, transfer the suspension to a centrifuge tube for centrifugation, wash it with anhydrous methanol 3 times to obtain the product ZIF-8-71-1-1 particles, prepare it into a butanol dispersion with a mass fraction of 10% without drying, and fully disperse it into a suspension by water bath ultrasound for 1.5h. Weigh 7.5g of the suspension and record it as liquid A for later use. Separately, 1.5 g of silicone rubber (hydroxypolymethylphenylsiloxane) was dissolved in 3.25 g of butanol and stirred thoroughly to prepare a silicone rubber solution, which was recorded as solution B and set aside.
[0067] Subsequently, 0.15 ml of liquid B was added to liquid A for pre-wetting, and liquid A was ultrasonically dispersed for 5 minutes using a probe ultrasonic instrument in an ice-water bath to further disperse it evenly. Subsequently, all of the liquid A treated with the probe ultrasonic instrument was added to the remaining liquid B while stirring. The obtained AB mixed solution was further ultrasonically dispersed for 10 minutes using a probe ultrasonic instrument in an ice-water bath to obtain a mixed matrix membrane casting solution, wherein the mass ratio of silicone rubber: butanol: biligand metal-organic framework material particles was 1:6.67:0.5.
[0068] An alumina-based membrane with a diameter of 18 mm and a thickness of 1 mm was immersed and pulled in the AB mixed solution obtained above. The immersion speed was 1 mm / s, the immersion time was 10 s, and the pulling speed was 1 mm / s. The mixed matrix membrane pulled from the casting solution was placed in an isooctane solution of tetraethoxysilane and dibutyltin dilaurate (composed of 0.3 g tetraethoxysilane, 0.4 g dibutyltin dilaurate and 10 g isooctane) for interfacial cross-linking to assemble the affinity molecule surface layer. The reaction temperature was 20°C and the reaction time was 1 h. An ultra-permeable membrane loaded with 50% ZIF-8-71-1-1 granular material and a cross-linking time of 1 h was obtained. Three ultra-permeable membranes were prepared in parallel using the above steps for performance testing. The test method is the same as in Example 1.
[0069] The performance test results of three parallel membranes are shown in Table 3 below. The test results show that the ultra-permeable membrane with a cross-linking reaction time of 1 h and a loading of 50% dual-ligand MOF particles also has excellent permeability.
[0070] Table 3
[0071]
[0072]
[0073] Example 4. Synthesis of a dual-ligand material ZIF-8-71-0.5-1.5 with a molar ratio of 2-methylimidazole to 4,5-dichloroimidazole = 0.5:1.5 and preparation of an ultra-permeable membrane loaded with 30% ZIF-8-71-0.5-1.5 granular material and a cross-linking time of 1 h
[0074] Weigh 0.53g zinc acetate dihydrate (Sigma-Aldrich, ≥98%) and dissolve it in 90ml anhydrous methanol solvent, stir and dissolve it as solution 1 for later use. Weigh 0.1g 2-methylimidazole (Sigma-Aldrich, ≥98%) and 0.5g 4,5-dichloroimidazole (Sigma-Aldrich, ≥98%) and dissolve it in 90ml anhydrous methanol solvent, stir and dissolve it as solution 2 for later use. Slowly add solution 1 dropwise to solution 2 and continue stirring, and react at a constant temperature of 25°C for 2h. After the reaction is completed, transfer the suspension to a centrifuge tube for centrifugation, wash it with anhydrous methanol 3 times to obtain the product ZIF-8-71-0.5-1.5 particles, which are not dried and prepared into a butanol dispersion with a mass fraction of 10%, and disperse it into a suspension by water bath ultrasound for 1.5h. Weigh 4.5g of the suspension and record it as liquid A for later use. Separately, 1.5 g of silicone rubber (hydroxypolymethylphenylsiloxane) was dissolved in 5.95 g of butanol and stirred thoroughly to prepare a silicone rubber solution, which was recorded as solution B and set aside.
[0075] Subsequently, 0.15 ml of liquid B was added to liquid A for pre-wetting, and liquid A was ultrasonically dispersed for 5 minutes using a probe ultrasonic instrument in an ice-water bath to further disperse it evenly. Subsequently, all of the liquid A treated with the probe ultrasonic instrument was added to the remaining liquid B while stirring. The obtained AB mixed solution was further ultrasonically dispersed for 10 minutes using a probe ultrasonic instrument in an ice-water bath to obtain a mixed matrix membrane casting solution, wherein the mass ratio of silicone rubber: butanol: biligand metal-organic framework material particles was 1:6.67:0.3.
[0076] An alumina-based membrane with a diameter of 18 mm and a thickness of 1 mm was immersed and pulled in the AB mixed solution obtained above. The immersion speed was 1 mm / s, the immersion time was 10 s, and the pulling speed was 1 mm / s. The mixed matrix membrane pulled from the casting solution was placed in an isooctane solution of tetraethoxysilane and dibutyltin dilaurate (composed of 0.3 g tetraethoxysilane, 0.4 g dibutyltin dilaurate and 10 g isooctane) for interfacial cross-linking to assemble the affinity molecule surface layer. The reaction temperature was 20°C and the reaction time was 1 h. An ultra-permeable membrane with a load of 30% ZIF-8-71-0.5-1.5 granular material and a cross-linking time of 1 h was obtained. Three ultra-permeable membranes were prepared in parallel using the above steps for performance testing. The test method is the same as in Example 1.
[0077] The performance test results of three parallel membranes are shown in Table 4 below. The test results show that the ultra-permeable membrane loaded with 30% ZIF-8-71-0.5-1.5 granular material and cross-linked for 1 h also has excellent permeability.
[0078] Table 4
[0079]
Claims
1. A super permeability separation membrane, characterized in that: The ultra-permeable separation membrane comprises an affinity molecule surface layer and an ultra-fast transmission layer.
2. The ultra-permeable separation membrane according to claim 1, characterized in that The affinity molecule surface layer is cross-linked polysiloxane or ionic liquid.
3. The ultra-permeable separation membrane according to claim 1 or 2, characterized in that: The thickness of the affinity molecule surface layer is 0-50 nm, and is not zero.
4. The ultra-permeable separation membrane according to claim 1, characterized in that The ultrafast transmission layer is a continuous nanoparticle layer of a dual-ligand metal-organic framework material with a particle size of 10-1000nm or a stacking layer of dual-ligand metal-organic framework nanosheets with a thickness of 1-100nm.
5. The method for preparing the ultra-permeable separation membrane according to claim 1, characterized in that: The steps include: (1) dispersing a dual-ligand metal-organic framework material in butanol to prepare a dispersion liquid, which is referred to as liquid A; dissolving silicone rubber in butanol to prepare a silicone rubber solution, which is referred to as liquid B; mixing liquid A and liquid B in an ice-water bath to obtain a mixed matrix membrane casting liquid; wherein the mass ratio of the silicone rubber, butanol, and dual-ligand metal-organic framework material is 1:2-10:0.1-0.8; (2) coating the mixed matrix membrane casting solution onto the alumina base membrane to obtain the mixed matrix membrane; (3) placing the mixed matrix membrane in an isooctane solution containing a silane coupling agent and a catalyst for interfacial crosslinking at a temperature of 15 to 30° C. for a time of 0.5 h to 72 h.
6. The preparation method according to claim 5, characterized in that: The preparation method of the dual-ligand metal-organic framework material comprises the following steps: (1) dissolving one of the nitrate, acetate or halide of divalent metal zinc or cobalt in anhydrous methanol and stirring uniformly to obtain a metal solution; (2) dissolving 2-methylimidazole and 4,5-dichloroimidazole in anhydrous methanol and stirring evenly to obtain a dual ligand solution; (3) mixing the metal solution obtained in step (1) with the dual ligand solution obtained in step (2), reacting at 20 to 30° C. for 0.5 to 24 hours, centrifuging the obtained product, and washing with anhydrous methanol to obtain a dual ligand metal-organic framework material; wherein the molar ratio of the divalent metal zinc or cobalt ion to the sum of 2-methylimidazole and 4,5-dichloroimidazole is 1:
2.
7. The preparation method according to claim 5, characterized in that: In step (1), the silicone rubber is hydroxypolymethylphenylsiloxane, and the method for preparing the mixed matrix membrane casting solution is specifically as follows: 3 to 5 drops of liquid B are added to liquid A, and ultrasonic dispersion is performed in an ice water bath to uniformly disperse the liquid A, and then all of the liquid A is added to the remaining liquid B, stirring while adding, and ultrasonic dispersion is performed to uniformly obtain the mixed matrix membrane casting solution; In step (2), the coating method is a dipping-pulling method, a spin coating method or a blade coating method. In step (3), the silane coupling agent is tetraethoxysilane, the catalyst is dibutyltin dilaurate, and the mass ratio of the silane coupling agent, the catalyst and the isooctane in the isooctane solution containing the silane coupling agent and the catalyst is 1:1 to 5:10 to 50.
8. The preparation method according to claim 7, characterized in that: The immersion-pulling method is specifically as follows: immersing the aluminum oxide-based membrane in a mixed matrix membrane casting solution and pulling it, with an immersion speed of 1 to 8 mm / s, an immersion time of 1 to 60 seconds, and a pulling speed of 1 to 8 mm / s.
9. The ultra-permeable separation membrane of claim 1 is used for enriching organic products of low-concentration alcohol or aldehyde in water.
10. The use according to claim 9, characterized in that: The mass concentration of the low-concentration alcohol or aldehyde in water is 0.01-10%, the alcohol includes methanol, ethanol or butanol, and the aldehyde includes furfural.
Citation Information
Patent Citations
Membranes
CN103842052A
Pervaporation membrane and preparation method thereof
CN107081068A
Dimethylpolysiloxane composite membrane and preparation method and application thereof
CN109621754A
Metal-organic framework material separation membrane as well as preparation method and application thereof
CN114425243A
Membrane and method for separation of organic compound
JP2008055326A